2020
DOI: 10.21273/horttech04724-20
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Environmental Health and Willingness to Compost Fresh Cut Floral Waste by Retail Flower Shop Owners

Abstract: In the United States there has been a push to convert industries to a more environmentally sustainable business attitude in recent years. Environmentally sustainable practices are not only good for the environment, but there is increasing evidence these practices lead to an increase in customer loyalty. The trend of self-regulation, willingly imposing more stringent environmental policies than required by the government, is progressing toward a time where environmentally friendly practices will be a competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A contact list of 1974 retail florists was used. The contact list was initially assembled in 2019 for a study investigating florist willingness to compost floral waste (Etheredge and Waliczek, 2020). The list was assembled by conducting a web-based search for retail florists in each of the 50 states.…”
Section: Samplementioning
confidence: 99%
“…A contact list of 1974 retail florists was used. The contact list was initially assembled in 2019 for a study investigating florist willingness to compost floral waste (Etheredge and Waliczek, 2020). The list was assembled by conducting a web-based search for retail florists in each of the 50 states.…”
Section: Samplementioning
confidence: 99%
“…A recent study that investigated United States consumers' perceptions of sustainable environmental attributes incorporated into business models of floral providers found that a majority of those surveyed were willing to pay up to 10% more for floral designs made from a more sustainable floral provider (Etheredge et al 2023). The same study also found that of the environmentally sustainable attributes that respondents were asked about, the use of locally sourced flowers was found to be the most influential change that a floral provider could make to increasing a consumer's willingness to purchase.…”
mentioning
confidence: 99%
“…Respondents also indicate a strong willingness to pay a premium to retail floral providers that dispose of floral waste through composting (Etheredge et al 2023). Research has indicated that the premium a consumer is willing to pay varies depending on the specific environmental attribute (Khachatryan et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation